Evolution of media space: communications between the society and authorities - Aryn Е.М.; Aryn Р.С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article examines the forms of historical development of communication between the authorities and society, analyzes the stages and conditions of their evolution in the aspects of countries and resources. The article classifies the levels of information and communication interaction of subjects of the media space in the most developed countries of the world. The article presents the specific results of information influence on the trends of political processes in such countries as the USA and Ukraine. Based on these results, the authors propose the implementation to improve the efficiency of the communicative functions of the authorities, enhancing the role of ‘transparency of state bodies’. The areas of modernization of the information design of the state, the involvement of Internet resources on social and political climate, the quality of civil society activity are analyzed in the present research. The conclusions made on the objectivity of transformation of mass communications, the liberalization of the professions of consensual and advisory participation of public institutions in decisionmaking procedures.